Religious Integration and the Development of Caodaism: An Overview - Alam, Mohammad Jahangir (Philosophy and Progress, 2024)
The formative stage of Cao Dai religion is closely connected to Vietnamese traditional myths, tales, doctrines and practices that are mostly transmitted orally down to the centuries. At the same time, Caodaism constantly maintained its links with religio-cultural elements of Chinese, Indian and Western origin. Due to this fact, Caodaism, with its synthesis of Eastern, Southeast Asian, Indian and Western elements specially from indigenous folk tales, Buddhism, Hinduism, Taoism, Confucianism, and Christianity, appeared as the religion of an acclaimed small group in 1926. This paper aims to examine how Caodaism evolved by a long-term process of Western and Asian acculturation. Thus, first to be considered is the significant role of socio- historical factors in creating a strong footing for the progress of Caodaism in Vietnam at the beginning of the early 20th century. Second, the process of Vietnamese acculturation is taken into consideration through which Caodaism borrowed diverse elements from different resources around it. Methodologically, a critical discourse analysis is adopted to consider the characteristics of Caodaism and its sociohistorical structure that is required to understand its historical origin and development. In conclusion, first, the study clearly demonstrates the close connection between Caodaism and the major factors of acculturation such as integration and assimilation for its development and diffusion around the South of Vietnam. Second, the current problem demands a careful consideration of some other crucial factors that might have influenced the rise and progress of Caodaism since its official journey in 1926. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 21-36